2004
DOI: 10.1007/s00280-004-0869-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of a fixed dose-rate infusion of gemcitabine associated with docetaxel in advanced non-small-cell lung carcinoma

Abstract: Prolonged gemcitabine infusion combined with docetaxel is well tolerated and its efficacy is similar to that of other chemotherapeutic schemes used for NSCLC treatment. However, the prolonged infusion of gemcitabine did not appear to result in any improvement in outcome or toxicity versus the standard dose rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…While gemcitabine is most commonly administered over a 30-min infusion, there is evidence to suggest that a prolonged FDR infusion may be more pharmacologically efficient [10,12,13] and the latter has shown promising results in phases I and II clinical trials for the treatment of NSCLC and pancreatic adenocarcinoma [11,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While gemcitabine is most commonly administered over a 30-min infusion, there is evidence to suggest that a prolonged FDR infusion may be more pharmacologically efficient [10,12,13] and the latter has shown promising results in phases I and II clinical trials for the treatment of NSCLC and pancreatic adenocarcinoma [11,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Phase II trials investigating the FDR gemcitabine infusion (10 mg/m 2 /min) in NSCLC have demonstrated promising efficacy with response rates ranging from 26% to 41% and median overall survival ranging from 7 to 13 months [14][15][16][17]. In these trials, the main toxicities that were more common with a prolonged infusion time were haematological, especially neutropenia and thrombocytopenia, however, it was usually reported that the FDR infusion had a manageable toxicity profile that was not dissimilar to that observed with the standard 30-min gemcitabine infusion.…”
Section: Introductionmentioning
confidence: 99%
“…De Castro et al assessed the FDR infusion of gemcitabine 1000 mg/m 2 on days 1 and 8, together with docetaxel 75 mg/m 2 on day 8, every 3 weeks in 50 NSCLC patients (60% in stage IV). In this trial, median PFS was 4 months, median and 1-year was 7 months and 25%, respectively, but it should be noted that 30% of patients were in ECOG PS 2 [27].…”
Section: Discussionmentioning
confidence: 91%
“…This customized approach according to the individual tolerability of each patient allowed to safely reach the optimal dosages of both drugs in half of the treated series [13]. On the other hand, the FDR infusion of gemcitabine is supported by early clinical evidences [19,20], and some pilot trials in NSCLC patients, assessing this modality of delivery either alone [22][23][24] or in combination with other active drugs [24][25][26][27]. Therefore, the present study was undertaken to ascertain which schedule of the combination of paclitaxel and gemcitabine, i.e., the intra-patient dose escalation, or the FDR of gemcitabine, could produce the longer FFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation